Mobile payment anomaly detection mechanism based on information entropy. Issue 1 (1st January 2016) - Zhang, Zhenjiang; Wang, Xiaoni; Sun, Lin
Abstract : With the rapid growth in the number of mobile phone users, mobile payments have become an important part of mobile e‐commerce applications. Secure payment systems directly affect the security of e‐commerce systems. This study proposes an anomaly detection mechanism supported by an information entropy method combined with neural network to improve mobile payments security. As the entropy value is sensitive and have much difference between normal and abnormal traffic flow in the mobile payment system, the abnormal traffic data will be detected. The simulation result shows that it can realise the effective monitoring of abnormal flow in the mobile payment system.